Can corporate ethics programs reduce unethical behavior?: threat appraisal or coping appraisal - Jannat, Taslima (Journal of business ethics, 2022)
While a corporate ethics program is expected to reduce employees’ unethical behavior, understanding the effects of the ethics program elements on reducing the unethical behavior is a crucial issue. This study aims to explore how a corporate ethics program with multiple control elements, including punishment, monitoring, internal reporting, code of ethics, ethics support service and ethics training, influence employees’ threat appraisal process, coping appraisal process and unethical behavior at workplaces. The data to verify proposed research hypotheses were collected by administering questionnaire survey on four autonomous government organizations in Bangladesh. Research findings show that only punishment and monitoring have significantly negative relationships with unethical behavior. Monitoring and internal reporting have significantly positive relationships with threat appraisal. The code of ethics, ethics support service and ethics training are associated positively with coping appraisal. The mediation results reveal that coping appraisal mediates the relationship between ethics program elements and unethical behavior; but the mediation effects of threat appraisal are not significant. This study provides valuable insights into how a corporate ethics program with multiple control elements reduces employees’ unethical behavior as well as how employees’ threat and coping appraisal processes are related to the corporate ethics program and unethical behavior in organizations.